EVALUATION OF THE EFFECT OF METFORMIN ON SERUM INFLAMMATORY BIOMARKERS (CRP, IL-6) IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (The Research of Medical Science Review, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is characterized by insulin resistance and low-grade systemic inflammation, which contributes to the progression of the disease and its complications. Metformin, a common first-line treatment for T2DM, is primarily known for its glucose-lowering effects, but emerging evidence suggests it may also modulate inflammatory biomarkers such as C-reactive protein (CRP) and interleukin-6 (IL-6).Objective: This study aimed to evaluate the effect of Metformin on serum levels of CRP and IL-6 in patients with T2DM and compare the outcomes with a control group.Study Design and Setting: A randomized controlled trial was conducted in Shalamar Medical & Dental College, Lahore from November 2024 to April 2025. Methodology: Seventy patients with T2DM were allocated to the Metformin group, and seventy patients were assigned to the control group. Baseline and post-treatment serum CRP and IL-6 levels were measured using enzyme-linked immunosorbent assays (ELISA). The Metformin group received 500 mg of Metformin twice daily, while the control group did not receive any specific treatment. Paired t-tests were used for within-group comparisons, and independent t-tests assessed differences between groups.Results: The Metformin group showed a reduction in both CRP (−2.35 ± 3.41) and IL-6 (−0.36 ± 3.28), while the control group showed a smaller reduction in CRP (−2.07 ± 3.92) and IL-6 (−0.77 ± 3.21). However, no significant differences were observed between the two groups (p > 0.05).Conclusion: The study found no significant effect of Metformin on serum CRP and IL-6 levels in T2DM patients over the 12-week period. Long-term studies with larger sample sizes are needed to explore Metformin's potential anti-inflammatory effects.